2020
DOI: 10.21203/rs.3.rs-89920/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

520YS , Encoding an Ankyrin Repeat Protein, is Involved in Chloroplast Development in Rice

Abstract: BackgroundThe ankyrin repeat (ANK) proteins are widely distributed in organisms ranging from viruses to plants, which play key roles in plastid differentiation, embryogenesis, chloroplast biogenesis and so on. However, only a few ANK genes have been identified in rice.ResultsIn this study, we isolated a yellow-green leaf mutant, 520ys, from japonica rice cultivar Nipponbare through ethyl methane sulfonate mutagenesis. The mutant exhibited a yellow-green leaf phenotype throughout the life cycle, arrested develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(43 reference statements)
1
0
0
Order By: Relevance
“…The A6147 marker is on the putative ankyrin repeat protein gene and the putative ankyrin repeat protein family is widely distributed among plants and has been found to participate in multiple processes, such as plant growth and development, hormone response, and response to biotic and abiotic stresses [ 47 ]. More importantly, this gene has been reported to be required for disease resistance [ 48 ], and it has been found that the markers we have identified are on same chromosomes previously identified by different researchers [ 49 ].…”
Section: Discussionsupporting
confidence: 54%
“…The A6147 marker is on the putative ankyrin repeat protein gene and the putative ankyrin repeat protein family is widely distributed among plants and has been found to participate in multiple processes, such as plant growth and development, hormone response, and response to biotic and abiotic stresses [ 47 ]. More importantly, this gene has been reported to be required for disease resistance [ 48 ], and it has been found that the markers we have identified are on same chromosomes previously identified by different researchers [ 49 ].…”
Section: Discussionsupporting
confidence: 54%